161 Current Practice of Antibiotic Prescription in Acute Uncomplicated Diverticulitis. (12th October 2021) - Patel, M; Darwish, N; Kirmani, N
Abstract: Aim: To review the current antibiotic prescribing practice for patients with acute uncomplicated diverticulitis against the NICE guidelines November 2019, to avoid unnecessary/overuse of antibiotics. Method: A retrospective review of patients presenting with lower abdominal pain between 1/11/2019 -31/1/2020. All patients with suspected diverticulitis were included. Patients who were subsequently diagnosed with complicated diverticulitis/alternate diagnosis were excluded from the analysis. Results: 22/27 (81.5%) of the patients were admitted. 26 out of 27 (96.3%) patients with acute uncomplicated diverticulitis were administered antibiotics. Antibiotics were indicated as per NICE guidelines in 17 patients (62.97%) and not indicated in 9 patients (33.34%). Admission was not indicated in 20 patients (90.91%) according to NICE guidelines. Conclusions: Our adherence to NICE guidelines is 66.67% in terms of antibiotic administration, however the drug and duration of antibiotic administration needs to be reviewed. NICE guidelines recommend that acute uncomplicated diverticulitis can be managed as an outpatient. Antibiotics should be administered only if patient is systemically unwell, is immunosupressed or has significant co morbidities